A multimodal concept for vaginal cuff closure by modification of the Bakay technique in total laparoscopic hysterectomy: a randomized clinical study - Üzeyir Kalkan; Kadir Bakay (BMC, 2022)
Abstract Background The aim of this study was to compare the outcomes of modified Bakay technique (MT) to standard colpotomy (ST) and cuff closure in total laparoscopic hysterectomy (TLH). Methods This two-centre, randomized-controlled study included a total of 160 patients who were scheduled for TLH for benign diseases (ClinicalTrials.gov Identifier is NCT05080114 and the first posted date was 15/10/2021). The patients were allocated into two groups by a computer-based randomization programme as ST group and MT group. Total operative time, cuff closure time, length of hospital stay, intra- and postoperative complications according to the Clavien-Dindo classification, pre- and postoperative vaginal length, and patient satisfaction according to the Patient Global Impression of Improvement (PGI-I) questionnaire were assessed. Results Seventy-seven patients in the ST group and 80 patients in the MT group underwent TLH. The total operative time was significantly shorter in the MT compared to the ST (55.5 vs. 59 min, respectively; p = 0.001). The median total operative time for colpotomy, extraction of uterus, and vaginal cuff closure steps was 9 (range 6-12 in MT vs. 6 to 11 in ST) min in both groups. The median hospital stay was 2 (range 1-4) days in both groups. Intraoperative blood loss was not significantly different between the groups (90 mL in ST vs. 80 mL in MT; p = 0.456). The mean uterine weight for the ST group and MT group was comparable (258.6 ± 88.6 g vs. 232.9 ± 102.5 g, respectively; p = 0.107). The preoperative vaginal length was not significantly different between the groups (p = 0.502). The median postoperative vaginal length was significantly higher in the MT group compared to the ST group on Day 90 (8 cm vs. 7,5 cm, respectively; p = 0.001). The PGI-I questionnaire score on Day 90 postoperatively was 2 (range 1-5) in both groups (p = 0.636). The complication rates were similar between the groups (p = 0.230). Conclusion The MT can be safely performed in most of the cases requiring TLH with the advantages of vaginal cuff closure before the alteration of pelvic anatomy, support to primary healing of the vaginal cuff, and routine concomitant apical support.